2018
DOI: 10.1051/matecconf/201818903002
|View full text |Cite
|
Sign up to set email alerts
|

A state of the art survey of data mining-based fraud detection and credit scoring

Abstract: Abstract.Credit risk has been a widespread and deep penetrating problem for centuries, but not until various credit derivatives and products were developed and novel technologies began radically changing the human society, have fraud detection, credit scoring and other risk management systems become so important not only to some specific firms, but to industries and governments worldwide. Frauds and unpredictable defaults cost billions of dollars each year, thus, forcing financial institutions to continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Table 10 presents a comparative summary of seven relevant SLRs and surveys performed in the area of fraud detection, including our contribution. In the "Context" column of Table 10, there are four SLRs that are exclusively related to some aspect of data mining [25,26,28,29], while only one is related to some aspect of fraud theory [75], in addition to other approaches [73,74]. The last row of Table 10 also presents information about the SLR covered in this document, the context of which explores both data mining and fraud theories together, unlike the other seven presented in this table.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 10 presents a comparative summary of seven relevant SLRs and surveys performed in the area of fraud detection, including our contribution. In the "Context" column of Table 10, there are four SLRs that are exclusively related to some aspect of data mining [25,26,28,29], while only one is related to some aspect of fraud theory [75], in addition to other approaches [73,74]. The last row of Table 10 also presents information about the SLR covered in this document, the context of which explores both data mining and fraud theories together, unlike the other seven presented in this table.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [26] concluded that most fraud-detection systems employ at least one supervised learning method and that unsupervised and semi-supervised learning methods are also used. The study showed that these techniques can be used alone or in combination to build more robust classifiers and that, without losing generality, these approaches are relatively successful in detecting fraud and credit scoring.…”
Section: Related Workmentioning
confidence: 99%
“…The LR, XGB, RF and DT algorithms are successful in detecting anomalies [6,18,22] however their main use in the current study is their ability to generalize, feature selection, interpretability [6,18,22,30] and further explain how the features contribute to the anomalous healthcare providers. This explanation was further achieved through the use of SHapley Additive exPlanation (SHAP) [13].…”
Section: Algorithmsmentioning
confidence: 99%
“…Common unsupervised methods include standard clustering methods, self-organizing map [39] and peer group analysis [37]. The interested reader is advised to consult [10,26,41] for more information.…”
Section: Related Workmentioning
confidence: 99%
“…The last category of classification techniques is semi-supervised learning which lies between supervised and unsupervised techniques, since it constructs predictive models using labeled samples together with a usually larger amount of unlabeled samples [13]. Some common semi-supervised methods are graph-based approaches, which consist in the creation of a graph model that reflects the relations included in the data and then transfers the labels on the graph to build a classification model [41]. Compared to the two other categories presented before, there are few publications about semi-supervised methods applied to card fraud detection.…”
Section: Related Workmentioning
confidence: 99%